Complex Dynamics of Glass-Forming Liquids : a Mode-Coupling Theory. - Gtze, Wolfgang (International series of monographs on physics., 2008)
Amorphous condensed matter can exhibit complex motions on time scales which extend up to those relevant for the functioning of biomaterials. The book presents the derivation of a microscopic theory for amorphous matter, which exhibits the evolution of such complex motions as a new paradigm of strongly interacting particle systems. e - ;The book contains the only available complete presentation of the mode-coupling theory (MCT) of complex dynamics of glass-forming liquids, dense polymer melts, and colloidal suspensions. It describes in a self-contained manner the derivation of the MCT equations.